“Shining a light on chronic pain”: A qualitative study of stakeholder views towards chronic pain at work and the Pain-at-Work Toolkit - Angela Claire Thornton; Elaine Wainwright; Wendy J. Chaplin; Victoria Abbott-Fleming; Daniel F. McWilliams; David A. Walsh; Gordon Taylor; Paul McNamee; Karen Walker-Bone; Holly Blake (PLoS ONE, 2026)
Purpose The study explored the views of organisational stakeholders who participated in the feasibility trial of the Pain-at-Work Toolkit towards the implementation of the toolkit in ‘real-world’ workplace settings. This digital toolkit was co-created with healthcare professionals, employers, and people with chronic pain and aimed to inform and enable individuals to self-manage their chronic pain at work. Design/methodology/approach A qualitative study using semi-structured interviews with 15 stakeholders from 12 organisations that participated in a feasibility trial of the Pain-at-Work Toolkit. Purposive sampling was used to ensure the inclusion of stakeholders with management or supportive roles who have responsibility for the health and wellbeing of employees. Findings The findings illuminate three key themes: not all disabilities are visible; not all line managers are equal; and who has control? These surmise that invisible disabilities such as chronic pain are underestimated, poorly understood, and inconsistently provisioned for in organisational policies. It highlights the key role that line managers play in employee disclosure and access to support but demonstrates that line managers vary in their delivery of support to employees. Lastly, it explores stakeholder perceptions of the roles of the employer relative to the employee with chronic pain. It confirms the need for additional resources to plug organisational gaps and give workers tools to self-manage their pain at work. Originality This study indicates the need for resources / supports to upskill line managers so they can intervene to proactively support employees with chronic pain to reduce sickness absence and presenteeism (working when unwell). The research demonstrates organisational stakeholders’ interest in a multi-faceted approach to help employees self-manage chronic pain in all types at work, such as that provided by the Pain-at-Work Toolkit. In addition, it clearly identifies the potential for complementary resources to educate and facilitate line managers to better support their staff.